INFLUENCE OF URINARY SCHISTOSOMIASIS ON NUTRITIONAL STATUS IN AL-MAJIRI (DISCIPLES) IN KAWO DISTRICT OF KADUNA METROPOLIS, KADUNA STATE-NIGERIA - Mohammed, Mahmood; A. Y., Umar,; P. A., Vanstawa,; Muktar, MuhammadDauda; Hassan, Amina Rabiu (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
A study on the influence of urinary schistosomiasis on nutritional status in Al-majiri was carried out to document the status of the disease and their nutritional status in Kawo District of Kaduna metropolis. Urine samples were from taken 360 Al-Majiris and analysed using the sedimentation method. Structured Knowledge, Attitude and Practice questionnaires were used determined age and water contact-related activities were administered and anthropometric measurements were to determine the nutritional status. A prevalence of 44.2% was recorded with mean intensity of 45.32 eggs/10ml of urine. The highest prevalence was recorded in the 10-14 age group while the lowest was recorded in the 20-24 age group. The age and water contact-related prevalence study revealed urinary schistosomiasis is greatly influenced by age and water contact. 30.8% of the respondent perceived Urinary schistosomiasis as a form of yellow fever. Body Mass Index (BMI) revealed that 63.3% of those infected are severely malnourished, BMI indicates a strong relation (P<0.05) between urinary schistosomiasis and malnutrition. It is suggested that in order to prevent urinary schistosomiasis, provision of portable drinking water, prevention of widespread wadding in pod water, adequate personal hygiene, improved nutrition and treatment of an infected persons to lessen the likelihood of water pollution should be encouraged.